The Influencing Factors of Dropout and Persistence of Central European Hungarian Minorities in Higher Educational Institutions - Sütő, Zsuzsanna (Central European Journal of Educational Research, 2020)
The statistics show that minority Hungarians’ education and participation in higher education, lags far behind the majority of society in Central Europe. Furthermore, we also know that the smaller the community, the more educated they are. The explanation for this could be, those who are less educated are more prone to assimilate. As a result, the existential question from these minority groups comes down to the growth of their level of education, a condition of which is university students’ acquisition of diplomas. Those factors deserve more scrutiny, in their identification, that increase the chances of getting a diploma. The goal of our study is (1) to identify the students who are persistent and at risk of dropping out, (2) to define the risk factors, and (3) at the same time to uncover the protective/ supporting factors as well. The theoretical background for our research was constituted by the institutional integrational model. The database used for this study contains data collected during a survey of Hungarian students from four different countries in Central Europe (IESA 2015, N= 2017). We found from our research that though the effect of intergenerational connections among students at Central European minority schools proved significant, the effect of place of residence, of settlement type, and of relationships within the family was even stronger.